An enhanced trilateration algorithm for indoor RSSI based positioning system using zigbee protocol - Rafina Destiarti Ainul (JURNAL INFOTEL, 2022)
Location information of the object based on wireless communication will play crucial role in several Wireless Sensor Network (WSN) applications. Some applications need to know the exact position of the object. The advantages of Zigbee as the part of Radio Frequency (RF) technology such as low cost, high scalability, high availability, and supporting topology for Indoor positioning system (IPS). In this paper, we propose IPS using Received Signal Strength Indicator (RSSI) based Zigbee protocol. The proposed approach is based on the enhancement of Trilateration algorithm. Basically, the main concept of the conventional trilateration is using three strongest RSSI from references node. However, the instability from measured RSSI influenced to its estimation result. Therefore quadratic weighted is adding to this proposed scheme as the enhanced trilateration algorithm. The estimated distance output from conventional trilateration algorithm will be used for calculating the weighted value and multiplying to each the reference node which produced lower estimation error. The simulation result show that using enhanced trilateration algorithm has capability to improve accuracy of estimated position up to 90.55 % with mean square error (MSE) 2.03 meters compared with only using conventional trilateration reached high estimated error up to 4.31 meters.